Effect of processing techniques on the overall quality attributes of cookies produced from jackbeans and wheat flour - A. O. Akinsola, O. A. Idowu (Journal of Scientific Agriculture, 2017)
The study was carried out to determine the effectiveness of heat processing on jackbeans, an underutilized legume. Raw and processed seed flour (roasted at 1200C for 10mins and pressure cooked for 10mins) produced from jackbeans were evaluated for its nutritional quality and antinutritional factors using standard methods. The nutritional qualities determined showed that sample with 20% pressure cooked jackbeans flour supplement has the highest amount of protein, fat, fibre and ash content, while the sample with 40% supplementation of pressure cooked jackbeans flour has the highest percentage of moisture content. The cookies produced from 100% wheat flour has the highest percentage of carbohydrate, while sample with 40% roasted jackbeans flour supplement has the highest percentage of concanavanine A. The antinutritional factors of the processed flours were found to be lower than the raw seed flour. Sensory qualities determined showed that sample with 20% of pressure cooked jackbeans supplement was rated high in terms of taste, aroma, texture, and overall acceptability, while cookies with 100% wheat flour was rated high 7.7 in term of colour. This study showed that thermal processing especially pressure cooking decreased the antinutritional contents of the jackbeans flour than other processing methods used.